Development and psychometric validation of a maternal competency assessment tool for family-based child health care - Endang Khoirunnisa; Tuti Rohani; Ruri Yuni Astari (Indonesian Institute for Counseling, Education and Theraphy, 2026)
Maternal competency plays a crucial role in ensuring optimal child health outcomes, yet comprehensive instruments for assessing maternal competency within family-based child health care remain limited. This study aimed to develop and psychometrically validate a maternal competency assessment tool for family-based child health care among mothers with infants and toddlers. A research and development design with a quantitative approach was employed. The instrument was developed through construct identification, item generation, expert validation, pilot testing, and field testing. Data were collected from March to June 2025 using an online questionnaire completed by 250 mothers in the Special Region of Yogyakarta, Indonesia, who were recruited through purposive sampling and met predefined eligibility criteria. Content validity was evaluated using the Content Validity Index with established psychometric criteria for item retention, while construct validity was examined using Exploratory Factor Analysis with a minimum factor loading of 0.40. Reliability was assessed using Cronbach’s alpha coefficient. The instrument demonstrated strong content validity (S-CVI/Ave = 0.92), a five-factor structure comprising 35 retained items that explained 68.47% of the total variance, and excellent internal consistency (Cronbach’s α = 0.93). The findings indicate that the developed instrument is a valid and reliable tool for assessing maternal competency in family-based child health care and may support educational evaluation, research, and maternal-child health programs.